PENGARUH DIRECT MARKETING METHODS TERHADAP KEPUTUSAN BERKUNJUNG DI KAMPUNG GAJAH WONDERLAND (Survei Pada Tamu Rombongan di Kampung Gajah Wonderland) - Labib, Muhammad; Gaffar, Vanessa (THE Journal : Tourism and Hospitality Essentials Journal, 2015)
Kampung Gajah Wonderland is one of the tourist destinations in Bandung. The number of visits in Kampung Gajah Wonderland increased from year to year but the target desired by management is still not reached. Therefore, the management of Kampung Gajah Wonderland do the direct marketing strategy methods consisting of direct mail, door to door selling and telemarketing. The purpose of this research was to obtain the findings regarding the extent to which the program's direct marketing methods, decision to visit Kampung Gajah Wonderland and how direct marketing strategy influences methods of visiting in Kampung Gajah Wonderland. The type of research used are descriptive and verifikatif with methods used is explanatory survey. The sample in this study as many as 75 groups with sample withdrawal technique used is systematic random sampling. Technique of data analysis used is path analysis.The independent variable in this study are direct mail (X1), door to door selling (X2), and telemarketing (X3) a dependent variable used is decisions while visiting (Y) which consists of product choice, brand choice dealer choice, purchase, amount, timing the purchase and payment method. Research results show that groups responses to direct marketing methods against the decision of a visit generally rated highly. A factor that gets the highest rating is door to door selling. While direct mail get the lowest value. Response groups regarding decisions been rated high. Gets the highest appraisal indicators is purchase timing. While the indicators are getting low value is payment method. Based on testing of SPSS 20 showed a simultaneous and partial correlation between direct marketing methods with visit decision. Based on this research, management’s Kampung Gajah Wonderland expected to increase selling door to door program in order to achieve the desired target.